Age related study of serum lipid peroxidation and antioxidant status - Adak, M; Nazri, S (Journal of Institute of Medicine Nepal, 2007)
Background : Ageing is a common phenomenan throughout the globe which is characterized by an impaired ability to maintain homeostasis under the condition of physiological stress. Some parameters in serum like malondialdehyde(MDA) , â-carotene, vita-E etc. are useful marker for chronological ageing. To validate the usefulness of the above parameters as an indicators for chronological ageing in Indian subjects. Materials and Methods: Blood samples were randomly collected from healthy 50 male and 50 female volunteers ranging in age 20-70 years who were coming for routine checkup to OPD in IGIMS, Patna. Fasting blood sample (10 ml) was collected from each individual for estimation of fasting blood sugar(FBS), malondialdehyde(MDA), Vita-E and â-carotene. Results: Serum MDA levels of these subjects were increased and lowering trend was observed in women. However, Vita-E levels were marginally decreased with age but no significant change in FBS levels were observed. An interesting observation was seen in â–carotene levels decreases markedly after attending the age of 40 years and the lowering tendency remain 70 years of age. Conclusion : A significant increased levels of MDA and decreased levels of â-carotene were useful marker for the study of chronological ageing in Indian subjects. Key words: Serum lipid peroxidation, ageing, malondialdehyde (MDA) The full text of this paper is available at Journal of Institute of Medicine website